Role of Marketing Concepts in Increasing Product Competitiveness - Musayeva Shoira Azimovna (Research Parks Publishers, 2021)
In this article, the content of the concept of consumer marketing today is also characterized by the choice of a specific target segment and its high quality, comprehensive service and the role of customer relationships.